2017
DOI: 10.1002/glia.23129
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking BCAS1, a novel myelin‐associated protein, display hypomyelination, schizophrenia‐like abnormal behaviors, and upregulation of inflammatory genes in the brain

Abstract: The abnormal expression and function of myelin-related proteins contribute to nervous system dysfunction associated with neuropsychiatric disorders; however, the underlying mechanism of this remains unclear. We found here that breast carcinoma amplified sequence 1 (BCAS1), a basic protein abundant in the brain, was expressed specifically in oligodendrocytes and Schwann cells, and that its expression level was decreased by demyelination. This suggests that BCAS1 is a novel myelin-associated protein. BCAS1 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…BCAS1 was originally identified as mRNA amplified in human cancer cell lines (17), but recent transcriptome studies have shown that it is also highly expressed in the brain and, more specifically, in oligodendrocytes (18). The function of BCAS1 is unknown, but there is evidence that it interacts with the dynein light chain (19) and is required for brain function because its absence results in reduced anxiety and schizophrenia-like behavioral abnormalities in mice (20).…”
Section: Introductionmentioning
confidence: 99%
“…BCAS1 was originally identified as mRNA amplified in human cancer cell lines (17), but recent transcriptome studies have shown that it is also highly expressed in the brain and, more specifically, in oligodendrocytes (18). The function of BCAS1 is unknown, but there is evidence that it interacts with the dynein light chain (19) and is required for brain function because its absence results in reduced anxiety and schizophrenia-like behavioral abnormalities in mice (20).…”
Section: Introductionmentioning
confidence: 99%
“…This help to explain why some ULK4 patients present severe learning difficulty and language delay (Liu, Guan, Shen, Flinter, et al, ). Schizophrenia‐associated myelin‐related genes including CNP , ERBB3 , GSN , MAL , MAG (Jungerius et al, ), and Bcas1 gene which display hypomyelination and schizophrenia‐like behaviours in mutants (Ishimoto et al, ) are all downregulated in Ulk4 hypomorph mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several myelin‐related genes, including CNP , ERBB3 , GSN , MAL , MAG and TF , are differentially expressed in schizophrenia post‐mortem brain tissue compared to unaffected controls (Jungerius et al, ). Mice lacking Bcas1 , a novel myelin‐associated protein interacting with F‐actin and the dynein light chain, exhibited schizophrenia‐like abnormal behavior, upregulated inflammation and hypomyelination (Ishimoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…7A. Based on enrichment analysis for DEGs with GO terms ( Supplementary Table 1) and literature (Han et al, 2012;Dashzeveg et al, 2014;Das et al, 2015;Ishimoto et al, 2017), DEGs were overrepresented in the categories 'Immune system', 'Development and proliferation', 'Extracellular matrix', 'RNA polymerase II transcription' and 'P53 mediated signaling' (Fig. 7B), suggesting these processes are differentially regulated between VWM and wt CNTF-mAstro.…”
Section: Mipsc-based Models Show Selective Involvement Of Astrocytic mentioning
confidence: 97%